A novel magnetic nanocatalyst Fe3O4@PEG–Ni for the green synthesis of 2, 3‐dihydroquinazolin‐4(1H)‐ones. (20th May 2020) - Noroozi Pesyan, Nader; Danandeh Asl, Aria; Namdar, Shadi
Abstract : Ni‐PEG (polyethylene glycol) complex supported on magnetic nanoparticle was created by grafting. The catalytic activity of Fe3 O4 @PEG–Ni was explored through one‐pot green synthesis of 2, 3‐dihydroquinazolin‐4(1 H )‐ones and used as an efficient and recoverable nanocatalyst. FT‐IR, XRD, EDS, BET, TGA, VSM and SEM techniques were employed to specify the nanocatalyst. This heterogeneous nanocatalyst demonstrated acceptable recyclability and could be reused several times with no considerable loss of its catalytic activity. Abstract : Fe3 O4 @PEG‐Ni as an efficient and recoverable nanocatalyst was created for one‐pot green synthesis of 2, 3‐dihydroquinazolin‐4(1 H )‐ones in excellent yield.